Monitoring rhizosphere microbial communities of tomato - Deery, Sarah Jane (2012)
Tomato is an economically important crop that can be devastated by many root infecting pathogens. The development of alternative and sustainable crop cultivation techniques and disease control methods is a must for the tomato industry, due to more strict government regulations and concerns over the sustainability of conventional chemical-intensive agriculture (Dixon and Margerison, 2009).